The cutoffs and performance of glycated hemoglobin for diagnosing diabetes and prediabetes in a young and middle-aged population and in an elderly population. Issue 2 (August 2015) - Yan, Shuang-Tong; Xiao, Hai-Ying; Tian, Hui; Li, Chun-Lin; Fang, Fu-Sheng; Li, Xiao-Ying; Cheng, Xiao-Ling; Li, Nan; Miao, Xin-Yu; Yang, Yan; Wang, Liang-Chen; Zou, Xiao-Man; et al.
Highlights Cutoffs of HbA1c were evaluated in two diverse population-based cohorts. HbA1c levels increased with age. Age-specific HbA1c cutoffs for detecting diabetes and prediabetes were appropriate. The performance of HbA1c as a diagnostic tool was poor.